2H/1H fractionation in microalgal lipids from the North Pacific Ocean: Growth rate and irradiance effects. (1st February 2019) - Wolfshorndl, Marta; Danford, Rebecca; Sachs, Julian P.
Abstract: The hydrogen isotope ratio ( 2 H/ 1 H) of microalgal lipids has become a useful tool for reconstructing hydrologic conditions in the geologic past from marine and lacustrine sediments. Culture studies have shown that, in addition to the 2 H/ 1 H ratio of growth water, parameters such as salinity, growth rate, and irradiance, can have a large effect on lipid 2 H/ 1 H ratios. But aside from salinity, these effects have not been well studied in the field. In this work, hydrogen isotope fractionation relative to growth water was measured in four algal lipids - C37:3 and C37:2 methyl alkenones, (3β, 4α, 5α, 22 E )-4, 23-Dimethylergost-22-en-3-ol (dinosterol), and 24-methylcholesta-5, 22E-dien-3β-ol (brassicasterol) – in the upper water column of two North Pacific Ocean locations. By comparing lipid 2 H/ 1 H variations as a function of depth at tropical Station ALOHA (22°45′N, 158°00′W) and mid-latitude Gyre (41°30′N, 132°00′W in the Transition Zone) it was possible to evaluate the H isotope effects of nutrient limitation and irradiance on natural phytoplankton populations by comparing measured fractionation factors (αlipid ) with those derived from laboratory-based empirical relationships. Significant distinctions were observed between the inferred causes of H isotope fractionation in different algal lipids at the two locations. At Station Aloha, 2 H/ 1 H fractionation in coccolithophorid-derived alkenones was primarily caused by nutrient-limited growth, while at Gyre it was caused by light limitation. Distinctions were less clear for the two sterols. 2 H/ 1 H fractionation in dinosterol was possibly influenced by nutrient-limited growth or light limitation at greater depths at both stations, while 2 H/ 1 H fractionation in brassicasterol matched values expected for nutrient-limited growth at both locations. Although systematic trends with depth in αlipid on the order of 10–30‰ were observed for each lipid, inter-day variability was some 3–7‰ depending on the lipid and site, and the magnitude of αlipid changes observed in the field were much less than those expected based on culture studies. This implies that the effects of nutrient and light limitation on natural phytoplankton populations in the ocean may not have a large influence on hydroclimate reconstructions based on 2 H/ 1 H ratios of microalgal lipids in marine sediments.